Metabotropic regulation of extrasynaptic GABAA receptors - Connelly, William M.; Errington, Adam C.; Di Giovanni, Giuseppe; Crunelli, Vincenzo (Frontiers in Neural Circuits, 2013)
A large body of work now shows the importance of GABAA receptor-mediated tonic inhibition in regulating CNS function. However, outside of pathological conditions, there is relatively little evidence that the magnitude of tonic inhibition is itself under regulation. Here we review the mechanisms by which tonic inhibition is known to be modulated, and outline the potential behavioural consequences of this modulation. Specifically, we address the ability of protein kinase A and C to phosphorylate the extrasynaptic receptors responsible for the tonic GABAA current, and how G-protein coupled receptors can regulate tonic inhibition through these effectors. We then speculate about the possible functional consequences of regulating the magnitude of the tonic GABAA current.